Differences in the Structure and Function of the Vestibular Efferent System Among Vertebrates - Cullen, Kathleen E.; Wei, Rui-Han (Frontiers in Neuroscience, 2021)
The role of the mammalian vestibular efferent system in everyday life has been a long-standing mystery. In contrast to what has been reported in lower vertebrate classes, the mammalian vestibular efferent system does not appear to relay inputs from other sensory modalities to the vestibular periphery. Furthermore, to date, the available evidence indicates that the mammalian vestibular efferent system does not relay motor-related signals to the vestibular periphery to modulate sensory coding of the voluntary self-motion generated during natural behaviors. Indeed, our recent neurophysiological studies have provided insight into how the peripheral vestibular system transmits head movement-related information to the brain in a context independent manner. The question then arises: what is the physiological role of the vestibular efferent system in mammals? We suggest that the mammalian vestibular efferent system does not play a significant role in short-term modulation of afferent coding, but instead plays a vital role over a longer time course, for example in calibrating the functional efficacy of vestibular circuits during development in a role analogous the auditory efferent system.